Relación entre sexismo ambivalente y satisfacción de parejas heterosexuales - Veyssal Palomino, Melihat (2024)
Ambivalent Sexism emerges as one of the issues that fosters and perpetuates gender inequality through its two components: hostile and benevolent sexism. This phenomenon is deeply rooted in culture, education, media, among others, and influences romantic relationships, having more detrimental effects on women and contributing to the systemic and structural inequalities they face. An applied review was conducted using two databases, incorporating specific inclusion and exclusion criteria, and ten studies were selected for analysis. Variability was found in the relationship between hostile sexism (HS) and relationship satisfaction; most studies support an inverse association between the variables. On the other hand, a positive yet insignificant correlation was observed between benevolent sexism (BS) and relationship satisfaction. Thus, it can be concluded that greater endorsement of hostile sexism may lead to lower satisfaction in heterosexual relationships. Additionally, mediating variables may contribute to the significance of benevolent sexism results. This information can inform preventive, promotional, and intervention actions within the framework of clinical psychology.